Development of Membraneless Sodium Perborate Fuel Cell for Media Flexible Power Generation. (27th March 2014) - Ponmani, K.; Durga, S.; Arun, A.; Kiruthika, S.; Muthukumaran, B.
Abstract : This paper reports the media flexibility of membraneless sodium perborate fuel cell (MLSPBFC) using acid/alkaline bipolar electrolyte in which the anode is in acidic media while the cathode is in alkaline media, or vice versa. Investigation of the cell operation is conducted by using formic acid as a fuel and sodium perborate as an oxidant for the first time under "acid-alkaline media" configurations. The MLSPBFC architecture enables interchangeable operation with different media combinations. The experimental results indicate that operating under "acid-alkaline media" conditions significantly improves the fuel cell performance compared with all-acidic and all-alkaline conditions. The effects of flow rates and the concentrations of various species at both the anode and cathode on the cell performance are also investigated. It has been demonstrated that the laminar flow based microfluidic membraneless fuel cell can reach a maximum power density of 28.2 mW cm −2 with a fuel mixture flow rate of 0.3 mL min −1 at room temperature.